Probiotic supplementation as a supportive treatment in inflammatory bowel diseases - literature overview - Alicja Grabarczyk; Martyna Grabowska-Szczurek; Jakub Rybak; Karol Magiera; Barbara Magiera; Piotr Bator; Michał Razik; Patrycja Rozwadowska (Kazimierz Wielki University, 2024)
Introduction and purpose: The human body hosts a diverse ecosystem of commensal microbes, known as the human microbiome. This review aims to asses the current state of knowledge regarding the effectiveness, mechanisms of action, and potential benefits of probiotic supplementation in patients with inflammatory bowel diseases. Materials and methods: A literature review was conducted using the "PubMed" and "Google Scholar" databases with the keywords "Probiotics", "Gut Microbiome", "Probiotics and the treatment of Crohns Disease", "Probiotics and the treatment of Colitis Ulcerosa". State of knowledge: Dysbiosis is known to disrupt the function of the intestinal mucosis and has been associated with chronic tissue inflammation. The use of probiotics is a promising method to improve the state of gut microbiota. It is known that the gut microbiome is disrupted in inflammatory bowel diseases.  Summary: The use of probiotics in Ulcerative Colitis is supported by a significant amount of evidence supporting its effectiveness. In the case of Crohn's Disease there is a lack of evidence to definitively determine whether the use of probiotics yields therapeutic benefits. Therefore there is a need for further research in this area.